Стекло - Скоренко Тим (Мастера интеллектуальной фантастики, 2021)
Экземпляры: аб. ЦБ (20240603) / Инвентарный номер: 21788 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: С 44 / ГРНТИ: 17.82 / ББК: 84(2Рос=411.2)6-4